RELIGIOSITAS ISLAM DALAM NOVEL CINTA DI UJUNG SAJADAH KARYA ASMA NADIA - Hera Nurcahyani; Hasanuddin WS; Novia Juita (Bahasa, Sastra, dan Pembelajaran, 2014)
Abstract: Islamic religiosity in the literature novels is one way to provide insight to the values ​​that have faded in the community. Islamic religiosity in the novel help shape the nation's personal character. This study aims to describe Islamic religiosity in this novel by Asma Nadia. Dimensions of religiosity analyzed consisted of aspects of theology, law, and morality.This research is content analysis by using descriptive methods. Literary works studied are novel by Asma Nadia. The novel was selected using purposive sampling technique. In analyzing  thedata, the writer carried out  three steps: (1) data reducing (Choosing, simplification, and transforming), (2) data display (data description and explain the data that have been reduced), and (3) make conclusion.The results showed that: (1) belief in the will of God, and prayers addressed to the Prophet, a discussion of the practice that can flow to those who have died is an aspect of faith found in the CDUS a Divine element, nubuwwah, spiritual, (2) implementation of worship pilgrimage and worship obligatory or sunnah prayers conducted figures, as well as the good relationship between the main character with a subordinate figures showed aspects of worship and muamalah law, (3) the attitude of patience, resignation, and thanks to God shows a moral aspect to God other than that, Cinta figures also being kind to the existing environment. These three aspects can be implicated in the learning of students in character education. Kata kunci : religiositas Islam, novel Cinta di Ujung Sajadah